2010
DOI: 10.1063/1.3435318
|View full text |Cite
|
Sign up to set email alerts
|

Spin wave resonance excitation in ferromagnetic films using planar waveguide structures

Abstract: We explore a new geometry allowing effective excitation of the lowest antisymmetric standing spin wave mode in ferromagnetic metallic films with symmetrical boundary conditions. The approach is based on the use of a coplanar waveguide with the ferromagnetic film, Permalloy (Py), playing the role of the signal line. In addition, we study a signal line which is a sandwich of Py inside two nonmagnetic metallic films. We find that the thickness and conductivity of the metal films can significantly alter the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Operation with exchange-dominated spin waves requires either precise nanotechnology [23][24][25] or more sophisticated approaches. 26,27 The dispersion relation of a ferromagnetic system can be studied numerically using micromagnetic simulations 18,19 as demonstrated in Refs. 5, 28, and 29.…”
Section: Spin Wave Modes: Simulation Detailsmentioning
confidence: 99%
“…Operation with exchange-dominated spin waves requires either precise nanotechnology [23][24][25] or more sophisticated approaches. 26,27 The dispersion relation of a ferromagnetic system can be studied numerically using micromagnetic simulations 18,19 as demonstrated in Refs. 5, 28, and 29.…”
Section: Spin Wave Modes: Simulation Detailsmentioning
confidence: 99%
“…The effect is somewhat similar to the direct injection of microwave currents into the planar sample. [32][33][34] In the latter case, a thickness-uniform microwave current across the sample thickness creates a microwave Oersted field whose profile is anti-symmetric in that direction. This field efficiently couples to standing spin wave resonances whose profiles are anti-symmetric across the thickness of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave conductivity contribution to the stripline broadband ferromagnetic resonance (FMR) response of highly-conducting (metallic) magnetic multilayers and nanostructures of sub-skin-depth thicknesses has attracted significant attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It has been shown that these effects are important when the microwave magnetic field is incident on only one of the two surfaces of a planar metallic material (see e.g.…”
Section: Introductionmentioning
confidence: 99%